The Role of Digital Communication Between Parents and Schools in Improving the Effectiveness of Student Attendance and Scholarship Administration at SMA XYZ - Fredy Harwanto; Rini Werdiningsih; Emiliana Sri Pudjiarti (International Journal of Humanities and Social Sciences Reviews, 2025)
This study aims to analyze the role of digital communication between parents and schools in improving the effectiveness of student attendance administration and scholarship management at SMA XYZ, and to identify factors influencing its implementation within a sustainable educational ecosystem. The research employed a narrative literature review approach with a comprehensive literature analysis from major academic databases, including Google Scholar and ProQuest Education Database, covering publications from 2010 to 2024. Data were collected through systematic searches using keyword combinations of digital communication, parent-school communication, educational technology, student attendance, scholarship administration, and family engagement, followed by thematic analysis to identify patterns and research gaps. Digital communication demonstrated high intensity (4.2/5 score) with WhatsApp as the dominant platform (65%). While 70% of parents increased their academic involvement, only 45% provided appropriate emotional support. Significant barriers included digital divide (30% infrastructure constraints), digital literacy gaps (25%), and boundary management issues (40% of teachers contacted outside working hours). Digital communication improved administrative transparency and real-time monitoring, though communication patterns remained predominantly unidirectional, with only 35% of parents providing active feedback. The study contributes to Digital Education Communication Theory by identifying paradoxes in digital parental engagement and confirming Digital Divide Theory in educational contexts. Findings expand Family Engagement Theory by revealing how real-time information access can create surveillance parenting behaviors that may be counterproductive to student well-being. Results indicate an urgent need for comprehensive digital communication policies, parent digital literacy programs, and infrastructure support to create an equitable and sustainable digital educational ecosystem that balances accessibility with professional boundaries.